EPIZOOTIK ENTOMOPATOGEN NOMURAEA RILEYI PADA CROCIDOLOMIA BINOTALIS DI KABUPATEN MAGELANG - , AHMAD SAEPULLAH; , Tri Harjaka, S.P., M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The cabbagehead caterpillar Crocidolomia binotalis Zell. is one of the most important pests on cabbage. Chemical synthetic insecticide was still use for controlling C. binotalis which cause negative effects to humans and the environment. One method to reduce the use of chemical synthetic insecticides is the utilization of the natural enemies of the pests. Entomopathogenic fungi (Nomuraea rileyi) is one of the natural enemies of C. binotalis and can cause high mortality (epizootic). This study aimed to determine the incidence of epizooticN. rileyi as a natural enemies of C. binotalis in Sawangan and Pakis, Magelang, Jawa Tengahin October 2012 until January 2013. The larvae of C. binotalis in cabbage was taken from 5 field (3 in Sawangan and 2 in Pakis). In the each areathe larvae was taken from 2 plants which had C. binotalislarvae more than 20 per-plants. Sampling larvae ofC. binotalis from the field taken 10 times at interval of 10 days during October 2012 until January 2013. Temperature, humidity and rainfall at the sampling site was observe when taking sample. The larvae of C. binotalis with cabbage from the field was taken to the Laboratory of Biological Control, Agriculture Faculty, Universitas Gadjah Mada and observed the larvae growth every 2 days until the larvae reach the imago phase. The larvae of C. binotalis which die before reach the imago phase was calculated and recorded the cause. The results of the larvae sampling and environmental conditions observation in the field suggested a relation between temperature and humidity changes with population of C. binotalis larvae. The mortality observation of C. binotalis larvae in the laboratory did not indicate a relation between population decline ofC. binotalislarvae in the field with infection ofN. rileyi. Mortality percentage of C. binotalis larvae cause by N. rileyiin the laboratory only 2.5 % in the 7th observation. Epizootic of N. rileyior natural enemy of C. binotalis did not occur in Sawangan and Pakis, Magelang, Jawa Tengah in October 2012 until January 2013 .